A graphical representation for the Integration of the C.O.S.T.A. Research Framework in teaching of Thematic Analysis for Postgraduate Students - Costa, King (My University, 2020)
Conducting Qualitative Data analysis is the most complex activity researchers are often confronted with. This is coupled with the fact that researchers are required to demonstrate each step taken in analyzing data and drawing conclusions. Ability to demonstrate methods enhances study credibility and believability of conclusions. This poster is a graphical representation of the content of a study by the author entitled, "Integrating the C.O.S.T.A. Research Framework in Teaching of Thematic Analysis for Postgraduate Students."
Keywords: C.O.S.T.A; Postgraduate Students